Hierarchical Fe2O3 nanotube/nickel foam electrodes for electrochemical energy storage. (20th October 2016) - Lin, Yan-Gu; Hsu, Yu-Kuei; Lin, Yu-Chang; Chen, Ying-Chu
Graphical abstract: Highlights: Fe2 O3 nanotube/nickel foam showed excellent specific capacitance. The pseudocapacitive mechanism was investigated via in-situ X-ray absorption spectroscopy. The composited nanoelectrode has acceptable cycling stability. Abstract: An iron-oxide (Fe2 O3 ) nanotube (NT) array is grown directly as a hierarchical nanoarchitecture on a nickel-foam (NF) surface via a simple and cost-effective immersive process. The morphology and microstructure of Fe2 O3 NT arrays are systematically examined by scanning electron, transmission electron, Raman, and X-ray photoelectron spectroscopies. The results reveal that the walls of Fe2 O3 NT are composed mainly of agglomerated small α-Fe2 O3 (hematite) monocrystalline nanoparticles filled with a few ZnO monocrystalline particles. The microstructural influence on the pseudocapacitive performance of the obtained Fe2 O3 NT/NF electrodes is also investigated via in-situ X-ray absorption spectroscopy (XAS) and electrochemical measurement. The in-situ XAS results regarding charge storage mechanisms of the Fe2 O3 NT/NF electrodes show that a Li + can reversibly insert/desert into/from the 3D mesoporous textures between the Fe2 O3 subunits depending on the applied potential. The electrochemical results indicate that the Fe2 O3 NT/NF electrode shows highly reversible features and satisfactory rate abilities. Most significantly, the excellent specific capacitance achieved in Fe2 O3 NT/NF nanoelectrodes is as great as 300.1 F g −1 ; energy density 75 W h kg −1 and power density 4.5 kW kg −1 are obtained, and the Fe2 O3 NT/NF nanoelectrode has acceptable cycling stability after 3000 cycles.